Contabilidade e tecnologias emergentes: Tendências na profissão, educação e modelo de negócio das empresas de contabilidade - Ferreira, P. A.; Marracho, A. (RISTI - Revista Ibérica de Sistemas e Tecnologias de Informação/Iberian Journal of Information Systems and Technologies (RISTI), 2022)
The purpose of this investigation is to identify trends, as a result of technological disruption, in the business models of accounting companies and in the skillset of accounting professionals, lato sensu, and to propose future guidelines for the education of those professionals. It analyzes direct data collected through interviews from four companies and indirect data found in 50 documents obtained from 30 websites, portals, blogs, YouTube channels and similar sources. It uses content analysis as data analysis technique. The results suggest that: (a) the accounting professional of the future must have a solid portfolio of technological, analytical and communication skills, (b) there is the need to rethink the curricula of accounting and similar courses and (c) the existence of various possibilities of business models provided they are (re)designed and (re)thought intelligently and based on five dimensions: (1) high use of technology, (2) high customer proximity, (3) relentless and proactive search for the most promising financial services, (4) intelligent segmentation and (5) focus on trust value.